STUDI KUALITATIF : ANALISIS KEBUTUHAN SISTEM INFORMASI KEGIATAN PEMBINAAN, PENGAWASAN DAN PENGENDALIAN (BINWASDAL) PUSKESMAS UNTUK PROGRAM KESEHATAN IBU PADA ERA KEBIASAAN BARU DI SUKU DINAS KESEHATAN JAKARTA PUSAT - Ita Ainy Ulfah (Jurnal Informasi Kesehatan Indonesia (JIKI), 2020)
Maternal Mortality Rate in Indonesia has not reached the SDGs target, so it is necessary to improve the quality of services for the Maternal Health program at the district level. One of the problems faced is the implementation of recording and reporting which is not optimal because the health information system is not yet integrated. The purpose of this study was to analyze the information system requirements for primary health care monitoring and supervision of Maternal Health Programs in the Central Jakarta Health Office. This type of research is qualitative research with thematic analysis . The Central Jakarta Health Office, as a regional unit that deals with health issues in Central Jakarta, has many limitations in the implementation of information and communication technology. With advances in information technology, the Health Office, which has the main tasks of supervision and monitoring of all health facilities, especially primary health care, must be able to develop an information system that can accommodate the activities that have been carried out so far. The information system developed must be integrated with all existing applications, both those developed by the Indonesian Ministry of Health, the DKI Jakarta Provincial Health Office, and the Primary Health Care unit. Keywords: maternal health program, monitoring and supervision, binwasdal, information system requirement